INTERACTIVE DIVERSITY: A PROPOSED MODEL OF CHRISTIAN ORIGINS - Hurtado, Larry (Journal of theological studies, 2013)
Although the 'trajectories' model of early Christian developments introduced by James Robinson and Helmut Koester has been influential in some circles, and particularly emphasizes diversity in early Christianity, the image of a trajectory may oversimplify matters and may in some cases impose an artificial connection of texts and phenomena. The undeniable diversity of early Christianity also involved a rich and varied interaction and a complexity that is not adequately captured in a 'trajectory' approach. A model of 'interactive diversity' more adequately reflects the complex nature of early Christianity.